Assessment of the effect of pelvic floor exercises on pelvic floor muscle strength using ultrasonography in patients with urinary incontinence: a prospective randomized controlled trial - Tosun, Ozge Celiker; Solmaz, Ulas; Ekin, Atalay; Tosun, Gokhan; Gezer, Cenk; Ergenoglu, Ahmet Mete; Askar, Niyazi (Soc Physical Therapy Science, 2016)
[Purpose] The aim of this study was to evaluate whether the effect of pelvic floor exercises on pelvic floor muscle strength could be detected via ultrasonography in patients with urinary incontinence. [Subjects and Methods] Of 282 incontinent patients, 116 participated in the study and were randomly divided into a pelvic floor muscle training (n=65) group or control group (n=51). The pelvic floor muscle training group was given pelvic floor exercise training for 12 weeks. Both groups were evaluated at the beginning of the study and after 12 weeks. Abdominal ultrasonography measurements in transverse and longitudinal planes, the PERFECT scheme, perineometric evaluation, the stop test, the stress test, and the pad test were used to assess pelvic floor muscle strength in all cases. [Results] After training, the PERFECT, perineometry and transabdominal ultrasonography measurements were found to be significantly improved, and the stop test and pad test results were significantly decreased in the pelvic floor muscle training group, whereas no difference was observed in the control group. There was a positive correlation between the PERFECT force measurement scale and ultrasonography force measurement scale before and after the intervention in the control and pelvic floor muscle training groups (r=0.632 and r=0.642, respectively). [Conclusion] Ultrasonography can be used as a noninvasive method to identify the change in pelvic floor muscle strength with exercise training.
Keywords: Pelvic floor muscle; Transabdominal ultrasonography; Urinary incontinence